Application of Industrial Pollution Projection System Model to Estimate the Pollution Level of Industries in Surabaya - Mulyarto, Aunur R.; Wijana, Susinggih; Wati, Iis Trisna (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
This research was intended to use IPPS model for estimating industrial pollution load in Surabaya. Descriptive-analytic method was chosen as the research methodology and consists of two main stages, i.e. classify industries base on the ISIC code and estimate pollution load of each industrial sector based on the number of employments’ variables. Major data used are the annual industrial activities provided by BPS. The data includes the name, addresses, main product and number of employees of the industries. The estimation has been carried out on six types of air pollutant, namely levels of SO2, NO2, VOC, CO, TSP, PM10 and two types of water pollutant (TSS and BOD). The result shows that the Chemical Producer N.E.C Industries are main contributor for the pollutant of SO2, NO2, and VOC, while TSP and PM10 are given mostly emitted by Oil and Fat Industries. On the other hand, the Soap, Cleaning Prep, Perfumery and Toilet Prep Industries are the main contributor for CO. The BOD pollution load comes mainly from Pulp, Paper and Paperboard Industries and the TSS is contributed primarily by Iron and Steel Mills, Foundries, and Re-Rolling Industries. Key Words: industrial pollution, pollution load